2018
DOI: 10.1111/jgh.14040
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiome alterations of healthy volunteers with proton pump inhibitor

Abstract: These results suggest that PPIs cause both oral and gut microbiota alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 38 publications
8
56
0
Order By: Relevance
“…Our study is consistent with the notion that H. pylori in the stomach has little or no effect on the bacterial diversity of the oral cavity [20]. The Shannon diversity index, ACE richness index, and Chao 1 richness estimator all declined after eradication of H. pylori compared to the baseline samples (p < 0.05), which was consistent with the prior studies that use of PPI and antibiotics may affect the oral microbiome [21,22].…”
Section: Discussionsupporting
confidence: 92%
“…Our study is consistent with the notion that H. pylori in the stomach has little or no effect on the bacterial diversity of the oral cavity [20]. The Shannon diversity index, ACE richness index, and Chao 1 richness estimator all declined after eradication of H. pylori compared to the baseline samples (p < 0.05), which was consistent with the prior studies that use of PPI and antibiotics may affect the oral microbiome [21,22].…”
Section: Discussionsupporting
confidence: 92%
“…Our study is consistent with the notion that H. pylori in the stomach has little or no effect on the bacterial diversity of the oral cavity (20). The Shannon diversity index, ACE richness index, and Chao 1 richness estimator all declined after eradication of H. pylori compared to the baseline samples (p<0.05), which was consistent with the prior studies that use of PPIs and antibiotics may affect the oral microbiome (21, 22).…”
Section: Discussionsupporting
confidence: 89%
“…A prospective investigation in 10 healthy adults showed that a 4‐week course of esomeprazole (20 mg once daily) decreased species diversity of saliva microbiota, while not significantly affecting species richness and community diversity of saliva or periodontal pocket microbiota. At the genus level, PPIs reduced Veillonella , Neisseria and Haemophilus abundances in the saliva and increased Fusobacterium and Leptotrichia in the periodontal pocket (Tables and ).…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort of 24 elderly, healthy individuals, a 14‐day course of omeprazole (20 mg once daily) did not affect faecal bacterial richness or diversity, but significantly reduced the abundance of Lachnospiraceae, Erysipelotrichaceae and Bifidobacteriaceae, while increasing the abundance of Streptococcaceae . Mishiro et al equally observed increased abundance of faecal Streptococcus levels after 4‐weeks of esomeprazole (20 mg once daily) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation